Towards resilient forest establishment in Europe: functional traits, genetic diversity and multifunctional design - Anastazija Dimitrova; Marcin Klisz; Enrique Andivia; Claudia Cocozza; Dušan Gömöry; Branko Kanjevac; Mathieu Lévesque; Barbara Mariotti; Jelena Milovanović; Andrea Piotti; Radosław Puchałka; Roberto Tognetti; et al. (New Forests, 2026)
Forest restoration and afforestation across Europe are accelerating, yet the decision-making processes governing forest establishment remain unevenly examined, especially from a biodiversity perspective. Considering this and the global environmental changes of climate shifts, land-use transitions, and biological invasions, the present review provides guidance for planning and establishment of multifunctional forests that enhance biodiversity outcomes without compromising long-term forest productivity or resilience. Aiming to assist both practitioners and researchers, we have particularly focused on tree species selection, plant production and management of forest reproductive material, and on-field establishment practices. Literature revision and expert observations indicate that tree species selection must integrate functional traits, provenance performance, and ecological impact assessments alongside species distribution models, since climatic suitability alone does not predict performance under future conditions. Genetic diversity remains severely underutilized in operational forestry but can be advanced through assisted migration, provenance mixing, and traceable seed sources as practices that need to be better supported and monitored. Concurrently, the plant production chain contains multiple points where genetic diversity is eroded, along with advancement opportunities explored through pan-European projects focusing on diversity standards, regional seed-exchange networks, and low-cost molecular monitoring. On-field, the choice between direct seeding and planting needs to link better genetic diversity targets and site conditions rather than biased preference. And finally, urban forests, increasingly recognized as components of the restoration continuum, require context-specific species selection and a transition from isolated specimen planting to more complex and inclusive design (similar to stand level in natural forests) to deliver meaningful biodiversity and multifunctionality outcomes.